Respuesta :
a + b = 15 ..... eq 1
a – b = 12 ...... eq 2
So a = 15 – b
Substitute in eq 2 :
15 – b – b = 12
15 – 2b = 12
–2b = 12 – 15
b = 1.5
So a = 15 – 3/2 = 13.5
4ab = 4 x 13.5 x 1.5 = 81
a – b = 12 ...... eq 2
So a = 15 – b
Substitute in eq 2 :
15 – b – b = 12
15 – 2b = 12
–2b = 12 – 15
b = 1.5
So a = 15 – 3/2 = 13.5
4ab = 4 x 13.5 x 1.5 = 81
Answer:
81
Step-by-step explanation:
here,
(a+b)=15 -------(1)
(a-b)=12 -------(2)
Equating the equation (1) and (2)
a + b = 15
a - b = 12
(b gets cancelled having opposite signs)
or, 2a = 27
or, a = 27÷2
a = 13.5
then, putting value of a in equation (1)
a+b=15
or, 13.5 + b=15
or, b=15-13.5
b=1.5
lastly,
4ab = 4×13.5×1.5
= 81
hope it helps!!